The Role of Metaphoric and Empirical Knowledge in the Process of Cognition - Shokhista Tuhtashevna, Makhmaraimova (International Journal of Psychosocial Rehabilitation, 2020)
Along with rational and empirical, metaphorical knowledge is recognized as a way of seeing, understanding the world around. Having an empirical beginning, the metaphor contributes to the structuring of the new in the language system. The nomination, as a product of speech activity, indicates a mechanism of thinking, defining the entire conceptual sphere of the conceptual picture of the world. The role of metaphor in the process of cognition is discussed this article. The author proves that by demonstrating a high informative capacity, affective saturation, the metaphor synthesizes integrity, establishing connections between structural components, structures thinking.